Studi Pembuatan Material Komposit Tahan Lentur dari Serat Ampas Tebu yang Digiling Halus untuk Komponen Automotif - Nusyirwan, Nusyirwan; Hizhar, Yul; Malik, Adam (Fakultas Teknik UMSU, 2025)
Composite material is one of the materials widely used in the field of construction engineering as a candidate for replacing metal materials. The advantages of this material include its low mass, ease of shape, and moisture resistance. However, this material still has many disadvantages, including low bending stress and easy to crack. Utilisation of waste materials such as bagasse which is worthless is one of the things that is very valuable, in this study we use it to be utilized as a high-value composite material to be used as the main material for making composite polymer materials in the field of engineering such as vehicles and ship hulls. In this study, we studied the flexural strength of composite materials from finely ground sugarcane fibre. From the test results, it is known that the flexural strength of the test material shows an increase in the variable of adding finely ground sugarcane fibre, the flexural strength increases from 10% to 20%, and after 20% the flexural stress value tends to decrease. The maximum flexural stress value was obtained with a mixture of finely ground sugarcane fibre with a percentage of 20% with a flexural stress value of 102.32 MPa, this value can increase the maximum flexural stress value of pure polyester by 42.52 MPa, showing an increase of 249.63%.